THE CRISIS OF TRUTH AND THE CALLING OF THE CHURCH: THE RELEVANCE OF FRANCIS SCHAEFFER'S ANALYSIS IN THE POST-TRUTH ERA - Elis; situmorang, Alexander (Sekolah Tinggi Teologi Pelita Hati, 2025)
Abstract: The contemporary world is experiencing a crisis of truth, characterized by the dominance of emotions, personal beliefs, and ideological narratives over objective facts and moral absolutes. This phenomenon, known as the post-truth era, has significant ethical, social, and theological implications, particularly for the Christian Church. Francis Schaeffer, a prophetic evangelical thinker of the twentieth century, provided a penetrating analysis of Western culture's departure from absolute truth in his seminal work,